Very late stent thrombosis after drug-eluting stent implantation in a patient with antiphospholipid syndrome - Hondo, Tatsuya (J Cardiol Cases, 2009)
A 74-year-old woman was admitted to our hospital with chest pain and shortness of breath. Coronary arteriograms revealed occlusion of a drug-eluting stent, which had been implanted 33 months earlier, in the middle right coronary artery. During percutaneous coronary intervention, distal embolization developed and a thrombus was detected with an aspiration catheter. Serological examinations performed 1 year before and during the present hospitalization revealed positive lupus anticoagulant activity. Thrombophilic tendencies, such as antiphospholipid syndrome, are noteworthy as one of the causative factors in very late stent thrombosis.